Comprehensive five-year study on salivary gland tumors: Demographic, clinical, and histopathological insights - Rahul Rajbhar; Dhanashri Ekatpure; Ashvini Kolhe (Advances in Oral and Maxillofacial Surgery)
Background: Salivary gland tumors account for 3 %–10 % of head and neck neoplasms. The aim of the study is to analyze demographic, clinical, and histopathological characteristics of salivary gland tumors. Materials and methods: A five year retrospective analysis of surgically excised salivary gland tumor specimens was conducted. Data on demographics, clinical features, and histopathology were reviewed and statistically analyzed using descriptive and inferential methods. Results: A total of 55,000 specimens were received; of these, 0.12 % was diagnosed as salivary gland tumors, with a male to female ratio of 1.1:1. Of the tumors, 85.1 % were benign and 14.9 % were malignant neoplasms, with the most common tumors being pleomorphic adenoma and mucoepidermoid carcinoma respectively. Benign tumors generally had a slower onset and were more encapsulated, while malignant tumors showed faster growth and were less encapsulated. Conclusion: This study enhances understanding of salivary gland tumors, highlighting benign predominance, gender disparities, and key histopathological features for diagnosis and treatment.